EXPRESSION ANALYSIS OF GENE GROUPS RELATED TO STRESS RESPONSE IN METATRANSCRIPTOMIC DATA OF CAVENDISH BANANA FRUIT BACTERIA (MUSA ACUMINATA, AAA) - Indira Laily Nurdin, Irishtsany
The use of chitosan as an edible coating can be done to inhibit the ripening of the fruit, but it needs further study regarding the effect of chitosan coating on the distribution and activity of bacteria that live in the banana fruit during ripening. The aim of this study was to analyze the effect of the maturation and coating of chitosan on the distribution profile of bacteria and on the gene expression of these bacteria, especially the genes belonging to the stress response group by using metatranscriptomic data. Metatranscriptomic data from the Cavendish banana (SRP300468) were processed by adapting the SAMSA2 pipeline. The RNA sequences were then cleaned from the rRNA to obtain mRNA data which were then annotated using the NCBI RefSeq database and the SEEDS Subsystem. Data processing ended with differential gene expression analysis using the DESeq2 tool. The results of the analysis show that Proteobacteria with a relative abundance in all samples of around 51-55%, Firmicutes with a relative abundance of around 18-19%, and Actinobacteria with a relative abundance of 12-14% are core taxa at the phylum level, while Staphylococcus with a relative abundance of 9.6- 11.4% and Acinetobacter with a relative abundance of 8.9-10.6% are core taxa at the genus level. Functional analysis showed that maturation caused more changes in the differential expression of bacterial functional genes compared to chitosan coating. The genes that play a role in tolerance to oxidative stress, osmolarity stress, and nutrient acquisition are stress response-related genes that experience significant changes in expression during maturation. This study also examines the glutathione metabolism pathway which is one of the pathways related to stress response. In this metabolic pathway, the genes that play an important role based on the amount of expression are glutathione peroxidase which is expressed dominantly by Acinetobacter in all samples with a percentage of 91-95%, and the enzyme glutathione S-transferase which on the first day of ripening is expressed dominantly by Novosphingobium as much as 33-34 %, whereas on the seventh day of maturation expressed dominant Thalassospira with a percentage of 28-33%. The overall results of the analysis show that the ripening and coating of chitosan do not change the composition and distribution of bacteria in bananas, but ripening will still bring about changes in differential gene expression related to the stress response as a form of bacterial adaptation.